An Experimental Investigation of ‘Drill-and-Practice’ Mobile Apps and Young Children - Herodotou, Christothea; Mangafa, Chrysoula; Srisontisuk, Pinsuda (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The choice of mobile applications (apps) for learning has been heavily relied on customer and teacher reviews, designers’ descriptions, and alignment with existing learning and human-computer interaction theories. There is limited empirical evidence to advise on the educational value of mobile apps as these are used by children. Understanding the impact of mobile apps on young children’s learning is timely given the lack of evidence-based recommendations that could guide parents and teachers in selecting apps for their children. In this paper, we present the results of a series of randomised control trial (RCTs) with 376 children aged 5 to 6 years old who interacted with two maths apps in three schools in the UK. Pre/post-test comparisons revealed learning gains in both the control and intervention groups, suggesting that the selected applications are equally good to standard maths practice. Implications for the selection and use of mobile apps are discussed.